2019
DOI: 10.1002/cphc.201900560
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Acetate on Au(111): An in‐situ Scanning Tunnelling Microscopy Study and Implications on Formic Acid Electrooxidation

Abstract: The adsorption of acetate on an Au(111) electrode surface in contact with acetic acid at pH 2.7 was imaged in‐situ using scanning tunnelling microscopy (STM). Two different ordered structures were imaged for acetate adsorbed in the bidentate configuration on the unreconstructed ()1×1 surface at 0.95 V (vs. the saturated calomel electrode, SCE). The first structure,(19×19)R23.45∘ , is metastable and transforms at constant potential within 20 minutes to a (2×2) structure, which is thermodynamically more favour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 82 publications
(186 reference statements)
1
15
0
Order By: Relevance
“…A similar effect has been observed during the oxidation of formic acid on Au(111) 30 and was attributed to a disorder-order transition within the formate adlayer at high coverage, as confirmed recently by comparing the behavior of formate with that of unreactive acetate on Au(111) electrodes. 31 As far as we know this is the first report of this phase transition in the formate adlayer also taking place on Pt(111) electrodes, although this process can also be identified in the recently- The same strategy can be used with Pt(100), although the high currents recorded for the direct oxidation may impede the observation of the adsorption process. As can be seen in Figure 2B and D, the qualitative evolution of the voltammogram is the same as that of Pt(111), however, faradaic currents are still not negligible for 30 V s -1 .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…A similar effect has been observed during the oxidation of formic acid on Au(111) 30 and was attributed to a disorder-order transition within the formate adlayer at high coverage, as confirmed recently by comparing the behavior of formate with that of unreactive acetate on Au(111) electrodes. 31 As far as we know this is the first report of this phase transition in the formate adlayer also taking place on Pt(111) electrodes, although this process can also be identified in the recently- The same strategy can be used with Pt(100), although the high currents recorded for the direct oxidation may impede the observation of the adsorption process. As can be seen in Figure 2B and D, the qualitative evolution of the voltammogram is the same as that of Pt(111), however, faradaic currents are still not negligible for 30 V s -1 .…”
mentioning
confidence: 75%
“…For Pt electrodes, the reaction rates for the intermediate pathway on Pt(111) are negligible, because a sufficiently high formate coverage happens only at potentials too positive for the step leading to the formation of CO through reduction of the monodentate adsorbed formate to be fast, whereas on Pt(100) there is a potential window where this reaction is possible at higher formate coverage. Evidence that oxidation of formic acid also proceeds through adsorbed monodentate formate on other metal surfaces has been provided in the case of Au [30][31][40][41] and Pd 42 electrodes, as well as for several metal surfaces at the solid-gas interface. [43][44][45][46][47][48] Cyclic voltammetry and DFT calculations suggested that the stabilization of monodentate adsorbed formate can take place by the presence of adatoms or other adsorbed species on the Pt surface, 21 and a similar effect has been proposed recently for Bi-modified Pd nanoparticles also supported by theoretical calculations.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] EDLs are a relevant subject in catalysis too. While their role in electrocatalysis is quite obvious, [9][10][11][12][13] there also exist EDL-related phenomena that can manifest in a catalytic process even without application of extraneous current-like electrocapillarity [14] and high viscosity of the layer. [15] Discussion of EDLs in scientific literature almost exclusively focuses on their formation via interaction of the solid with the background electrolyte by adsorption of ions from the latter.…”
Section: Introductionmentioning
confidence: 99%
“…EDLs are a relevant subject in catalysis too. While their role in electrocatalysis is quite obvious, there also exist EDL‐related phenomena that can manifest in a catalytic process even without application of extraneous current—like electrocapillarity and high viscosity of the layer …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, electrode kinetics is greatly influenced by adsorption energies of intermediates and often also by adsorbed electrolyte components, which in many cases are extremely sensitive to the local atomistic structure. Thus, the arrangement of surface atoms at the metal electrode may have a profound effect on the energetic pathways from reactants to products and, accordingly, the reaction rate, activity and selectivity [3,7,8].…”
Section: Introductionmentioning
confidence: 99%